Development & Performance Testing of Domestic Air-Conditioner - Chaturvedi, Lakshya (My University, 2023)
This master's thesis aimed to investigate and improve the performance of existing cooling systems and develop innovative solutions to address emerging challenges in the Residential Air Conditioning (RAC) industry. The research began with a comprehensive literature review, which provided a foundation for understanding the latest technologies and identifying areas for improvement. Experimental investigations were conducted to analyse the performance characteristics of various systems, collecting data on energy efficiency, cooling capacity, and overall system performance. Advanced control algorithms, optimised system designs, and integration emerging technologies were proposed as innovative solutions to enhance energy efficiency, reduce environmental impact, and improve user comfort. Close collaboration with LG Electronics' R&D team ensured valuable insights and feedback throughout the research process. Testing was performed in the company's labs following strict standards set by governmental bodies, ensuring compliance with regulatory requirements. Multiple stages of testing were conducted, and the results consistently remained in internal limits set by LG Electronics, with margins maintained within 5%. The performance and capacity results were compared to benchmark companies, ensuring healthy competition and confirming the competitiveness of the developed models. Machine-to-machine variation was also assessed and found to be within the acceptable three-sigma limit. The significant findings of this research highlight the successful development of new air conditioner models that replace previous ones. The modifications, including introducing additional functions and a new tubing design, resulted in improved cooling capacity with relatively lower energy consumption. The detailed procedure of the performance parts selection, as per LG Electronics standards, was recorded and implemented throughout the research process. The outcomes of this research contribute to the advancement of refrigeration and air conditioning technologies, benefitting LG Electronics and offering valuable insights to the broader industry to develop more efficient and environmentally friendly cooling systems.
ME Thesis
Keywords: Domestic Air-Conditioner; ISEER; Performance; Testing; Standards